Tolmačenje v Evropski uniji - Maček, Amalija (Teorija in praksa, 2014)
The Translation Department at the University of Ljubljana's Faculty of Arts has been training conference interpreters for EU institutions for a number of years. In this process, it has cooperated closely with the European Parliament's Directorate-General for Interpretation (GD INTE), as well as the joint translation service of the European Commission and Council (SCIC). Both institutions offer the Translation Department financial and teaching assistance, and the department seeks to prepare interpreters to directly enter this demanding practice in a relevantly short time. This article is primarily dedicated to the challenges of education and interpreting for Council needs.
Keywords: European Union; Evropska unija; interpretation; interpreter training; izobraževanje tolmačev; pedagoška asistenca; prehod v prakso; SCIC; teaching assistance; tolmačenje; translation in practice